2006
DOI: 10.2174/138161206775474242
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria: A Target for Neuroprotective Interventions in Cerebral Ischemia-Reperfusion

Abstract: Evidence obtained over the past two decades shows that reactive oxygen species (ROS) are involved in brain lesions, including those due to cerebral ischemia-reperfusion. The mitochondria are the primary intracellular source of ROS, as they generate huge numbers of oxidative-reduction reactions and use massive amounts of oxygen. When anoxia is followed promptly by reperfusion, the resulting increase in oxygen supply leads to overproduction of ROS. In ischemic tissues, numerous studies have established a direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(116 citation statements)
references
References 202 publications
(233 reference statements)
6
110
0
Order By: Relevance
“…Previous studies have demonstrated that ischemic postconditioning reduces the overproduction of reactive oxygen species and calcium overload, both of which contribute to mitochondrial dysfunction and cytochrome c release. 7,[32][33][34][35] It has been reported that neuron death in the penumbra after focal ischemia is mainly induced via apoptosis, and ischemic postconditioning decreases terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling-positive neurons in the penumbra. 7 Therefore, we speculate that ischemic postconditioning inhibits the release of cytochrome c and the activation of caspases and then blocks I/R-induced neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that ischemic postconditioning reduces the overproduction of reactive oxygen species and calcium overload, both of which contribute to mitochondrial dysfunction and cytochrome c release. 7,[32][33][34][35] It has been reported that neuron death in the penumbra after focal ischemia is mainly induced via apoptosis, and ischemic postconditioning decreases terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling-positive neurons in the penumbra. 7 Therefore, we speculate that ischemic postconditioning inhibits the release of cytochrome c and the activation of caspases and then blocks I/R-induced neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although more and more studies demonstrate the ischemia mechanism, such as excessive production of free radicals (Chung et al, 2006;Margaill et al, 2005), altered calcium homeostasis (Montell, 2005) and N-methyl-D-aspartate excitotoxicity (Christophe and Nicolas, 2006), few effective therapeutic drugs have been used in clinic.…”
Section: Introductionmentioning
confidence: 99%
“…3 Damage of mitochondria leads to cell death, because mitochondria are involved in energy metabolism and calcium homeostasis as well as the ability of mitochondria to release apoptotic-promoting proteins such as cytochrome C and apoptosis-inducing factor to initiate the intrinsic pathway of apoptosis. 5 Ample evidences have suggested that mitochondria have a central role in neurodegenerative disease.…”
mentioning
confidence: 99%